PENGEMBANGAN PURWARUPA ALAT BANTU PENGANGKATAN UNTUK AKTIVITAS PENANGANAN MATERIAL - Ryandra Wijaya, Rifki
On the spring bed production floor at PT X, human power still used to carry out material handling activities, such as lifting objects manually. One of the main problems that often occur in such physical activity is the risk of work-related musculoskeletal disorders (WMSDs). To mitigate the risks, there are various lifting aids developed by researchers. One of which is named personal lift-assist device (PLAD), pioneered by Abdoli-Eramaki and the team at Queen's University of Canada. PLAD consists of elastics component on the thighs and back that can support muscle force during lifting activities. Although this lifting aid has proven its effectiveness in various studies, there are issues and development potentials that can be further researched about this assistive device. Therefore, this research aims to develop previous PLAD research by considering the aspect of ergonomics as an effort to reduce the risk of WMSDs in PT X. The development of the lifting aid is done using the design thinking method with five stages, namely empathize, define, Ideate, prototype, and test. The developments include; improving tool’s size adjustment mechanisms, looking for better component alternatives, and adding elastic component extensions on the arm. The prototype was then tested with participants to assess usability. Then, its performance was tested through a 5 kg load-lifting simulation experiment. Variables measured include; Cardiac Stress index (CSI) as an indicator of physical workload, Borg's rating of perceived exertion (RPE) as an indicator of psychophysical perception, as well as sagittal head angle (HT), cervical angle (CV), and shoulder angle (SH) as a health indicator of neck and shoulder posture. Based on statistical test results, the use of this lifting aid prototype can significantly decrease the value of CSI and RPE (P-value<0.05). This indicates that the prototype of the assistive device can effectively reduce the physical workload during lifting activities. In addition, there is no significant difference in the posture angle from the use of the prototype.